Long-Term Surgical Outcomes of Two Patients with Intracranial Extraskeletal Mesenchymal Chondrosarcoma and a Brief Literature Review - Abdallah, Anas (Asian Journal of Neurosurgery, 2022)
Objective Intracranial extraskeletal mesenchymal chondrosarcomas (IEMCs) are malignant aggressive neoplasms. IEMCs originate from the meninges or parenchyma. In the current study, we aimed to figure out the importance of gross total resection (GTR) and adjuvant radiotherapy (RT) by evaluating all reported IEMCs through the literature that included our two patients.Methods and Methods We presented two IEMC patients who were treated at our institutions and followed up for a long duration. To understand the appropriate management for IEMC, we conducted a systematic literature review for previously reported series and cases of IEMCs.Results We surgically treated two young males with IEMC initially diagnosed at their age of 18 and 20 years. The patients were initially treated with GTR and GTR followed by RT, and followed-up for 218 and 73 months, respectively. Through both the patients, we obtained 83 reported IEMC patients from the literature. The mean age of the reported cases was 24.5 ± 16.0 years (2 months–71 years). Female predominance was 54.2%. The mean progression-free and overall survivals were 27.9 and 39.0 months, respectively. The progressiveness rate was 56%. The presence of progressiveness was a poor prognostic factor (p = 0.0008). GTR was achieved in 53.0% of the patients. There was a significant difference between patients who received GTR compared with those who did not receive GTR (p = 0.035).Conclusion Regarding their malignancy and progressiveness, we recommended the maximal surgical resection with wide margins followed by RT as appropriate management for IEMCs with close follow-up. The timely treatment provides high life quality and avoids life-threatening complications.
Keywords: intracranial extraskeletal mesenchymal chondrosarcoma; gross total resection; radiotherapy